Open innovation model for a large company in the ICT industry: Case Ericsson LMF - Pinoargote, Juan (My University, 2014)
Open innovation paradigm states that the boundaries of the firm have become permeable, allowing knowledge to flow inwards and outwards to accelerate internal innovations and take unused knowledge to the external environment; respectively. The successful implementation of open innovation practices in firms like Procter & Gamble, IBM, and Xerox, among others; suggest that it is a sustainable trend which could provide basis for achieving competitive advantage. However, implementing open innovation could be a complex process which involves several domains of management; and whose term, classification, and practices have not totally been agreed upon. Thus, with many possible ways to address open innovation, the following research question was formulated: How could Ericsson LMF assess which open innovation mode to select depending on the attributes of the project at hand? The research followed the constructive research approach which has the following steps: find a practical relevant problem, obtain general understanding of the topic, innovate the solution, demonstrate the solution works, show theoretical contributions, and examine the scope of applicability of the solution. The research involved three phases of data collection and analysis: Extensive literature review of open innovation, strategy, business model, innovation, and knowledge management; direct observation of the environment of the case company through participative observation; and semi-structured interviews based of six cases involving multiple and heterogeneous open innovation initiatives. Results from the cases suggest that the selection of modes depend on multiple reasons, with a stronger influence of factors related to strategy, business models, and resources gaps. Based on these and others factors found in the literature review and observations; it was possible to construct a model that supports approaching open innovation. The model integrates perspectives from multiple domains of the literature review, observations inside the case company, and factors from the six open innovation cases. It provides steps, guidelines, and tools to approach open innovation and assess the selection of modes. Measuring the impact of open innovation could take years; thus, implementing and testing entirely the model was not possible due time limitation. Nevertheless, it was possible to validate the core elements of the model with empirical data gathered from the cases. In addition to constructing the model, this research contributed to the literature by increasing the understanding of open innovation, providing suggestions to the case company, and proposing future steps.